Prevalence of Diabetes Mellitus among Patients with Tuberculosis and Its Associated Factors in Sana'a, Yemen, 2021 - Sumia Alturki; Mohammed Al Amad; Esam Mahyoub; Noora Al Hanash; Abdulbary Alhammadi (MDPI AG, 2023)
Diabetes mellitus (DM) is one of tuberculosis' (TB) ending barriers. TB patients with DM are at a higher risk than non-diabetes patients to develop complication, relapse and die. In Yemen, information on TB-DM comorbidity is lacking. This study aimed to determine the prevalence and associated factors of diabetes among TB patients at the National Tuberculosis Center (NTC) in Sana'a. A facility-based cross-sectional study was conducted. All TB patients aged >15 years who attended the NTC from July to November 2021 were screened for DM. Socio-demographic and behavioral information were collected through face-to-face interviews using questionnaires. A total of 331 TB patients were enrolled, 53% were males, 58% aged <40 years, and 74% were newly diagnosed with TB. Overall, DM prevalence was 18%. Higher rates of DM were found among TB patients that were male (OR = 3.0; 95% CI; 1.4-6.7), ≥50 years of age (OR = 10.8; 95% CI; 4.3-27.3), and those with a family history of diabetes (OR = 3.4; 95% CI; 1.6-6.9). Almost one fifth of TB patients had DM. The early detection of DM through immediate screening after a TB diagnosis and periodically during the course of treatment is crucial for TB patients' optimal care. Dual diagnostics for reducing the dual burden of TB-DM comorbidity is recommended.